Isolation, Identification and Characterization of the Surface Glycoprotein of Myxobolus koi - Insariani Insariani; Khumaira Puspasari; Haririyah Haririyah; Emei Widiyastuti; Chusnul Chotimah; Hastari Wuryastuti (Jurnal Sain Veteriner, 2012)
Myxobolus koi is considered to be one of the pest diseases of  fish quarantine class I, which has to be destroyed if it is found. Technique that is regularly used for diagnosis M. koi, such as histopathological examination, polymerase  chain reaction (PCR) and sequencing always done in dead fishes. The objective of this study was to isolate the protein of M. koi as the initial step for producing antibody that can be used as a material for immunology-based diagnostic method. In the present study. identification of surface protein of M. koi involved three different stages. The first stage was to isolate and identify M. koi from koi fish using wet mount, and histopathologic, PCR and sequencing techniques. In the second stage, purification and isolation of the surface protein of M. koi  was done by Percoll gradient ultracentrifugation technique. Purification using the technique produced 5 different layers on the surface of the tube . Myxobolus koi spores were found in the 2nd, 3rd and 4th layers. The third stage was to identify and characterize the surface protein of M. koi using SDS PAGE. The results of SDS PAGE analysis showed that spores purified from 3 different layers all have the same profiles. Molecular sizes of the surface protein of M. koi that could be isolated in this study were 12 Kd, 16 Kd, 25 Kd, 27 Kd, 40 Kd and 45 Kd. Among them, the molecular sizes of 12 Kd, 25 Kd and 27 Kd could be seen clearly.Keywords: Myxobolus koi, surface glycoprotein, isolation, Percoll gradient centrifugation, SDS PAGE